Optimization of Transport Networks - Steenbrink, P. A. (London: New York: Wiley, 1974)
In this book, the transport network optimization problem is stated mathematically and then an extensive and detailed survey of the most important and best-known methods of solving this problem is given.
"A Wiley-Interscience publication."
Includes bibliographical references.
ne 23/02/2018
Loan
Keywords: Transportation; Mathematical Optimization